OCCUPATIONAL STRESS AS A PREDICTOR OF GENERAL WELL-BEING OF PREGNANT WOMEN IN BENUE STATE - Eze, Uchenna Gerald; Omeke, Sarah Chinaza; Okoli, Paul Chibuike; Enukora, Nkiru Abumchukwu; Eze, Stephen Chijioke; Onah, Livinus Nnanyereugo; Maduka, Chike Joachim; Mba, Gabriel Sunday; Eya, Jonathan Chukwuemeka; Onah, Ikedichukwu Luke; Ozougwu, Augustine Obumneme; Ugwu, Chika Gloria; et al. (African Journal of Social and Behavioural Sciences, 2025)
The role stress plays in the general well-being of people has been a thing of major concern to health providers. This study examines the occupational stress on the general well-being of pregnant women in Benue state. It employs an ex-post-facto design. 370 pregnant women attending anti-natal clinic were sampled using multi-stage sampling technique from three geopolitical zones of Benue State: Markudi 157(42%), Otukpo 123(33.2%), and Kastina – Ala 90(24.3%). Their age ranged between 18 and 43 years, with a mean age of 1.63 and a standard deviation of 0.48. Two instruments were used for data collection namely, the Job Related Tension Scale and the General Well-being Questionnaire. One hypothesis was generated and tested using regression analysis. Findings revealed that occupational stress predicted the general well-being of pregnant women [F (1,369) = 11.744, P<.01]. On the dimensions of general well-being, occupational stress predicted general health [F (4,369) = 10.559, P<.01] anxiety [F (4,369) = 9.406, P<.01] self-control [F (4,369) = 4.174, P<.05] depression [F (4,369) = 16.926, P <.05) and positive well-being [F (4,369) = 9.041, P<.01] but did not predict vitality [F (4,369) = 6.024, P>.05] among pregnant women in Benue State. It was concluded that stress at the workplace is a potential variable that can contribute immensely to the general well-being of pregnant women in Benue State. Based on these findings, it was recommended that pregnant women in Benue state should be actively involved in activities that are somehow stressful in order to enhance their general well-being.